(untitled) (AmeriQuests, 2022)
While Temporary Protection Status has been put forth as a possible solution to the current Ukrainian Refugee crisis, Subsidiary Protection stands as the more prudent tool in fulfilling Member State obligations and asylum seeker need in the midst of currently indefinite conflict.